The Complex Role of Regulatory T Cells in Immunity and Aging - Rocamora-Reverte, Lourdes; Melzer, Franz Leonard; Würzner, Reinhard; Weinberger, Birgit (Frontiers in Immunology, 2021)
The immune system is a tightly regulated network which allows the development of defense mechanisms against foreign antigens and tolerance toward self-antigens. Regulatory T cells contribute to immune homeostasis by maintaining unresponsiveness to self-antigens and suppressing exaggerated immune responses. Dysregulation of any of these processes can lead to serious consequences. Classically, regulatory T cell functions have been described in CD4+ T cells, but other immune cells also harbour the capacity to modulate immune responses. Regulatory functions have been described for different CD8+ T cell subsets, as well as other T cells such as gamma/delta T cells or NKT cells. In this review we describe the diverse populations of regulatory T cells and their role in different scenarios. Special attention is paid to the aging process, which is characterized by an altered composition of immune cells. Regulatory T cells can contribute to the development of various age-related diseases but they are poorly characterized in aged individuals. The huge diversity of cells that display immune modulatory functions and the lack of universal markers to identify Treg make the expanding field of Treg research complex and challenging. There are still many open questions that need to be answered to solve the enigma of regulatory T cells.